Trabectedin plus pegylated liposomal doxorubicin in patients with disease progression after PARP inhibitor maintenance: a real-life case–control study. Issue 2 (23rd December 2022) - Vertechy, Laura; Boccia, Serena Maria; Tiberi, Giordana; Avesani, Giacomo; Corrado, Giacomo; Fagotti, Anna; Scambia, Giovanni; Marchetti, Claudia
Abstract : Objective: Poly (ADP-ribose) polymerase (PARP) inhibitor resistance is problematic in epithelial ovarian cancer management and sequencing strategies may be performed to overcome this issue. In this context, our study evaluated the role of non-platinum doublet pegylated liposomal doxorubicin/trabectedin in ovarian cancer platinum-sensitive patients who experienced disease progression under PARP inhibitor maintenance. Methods: This case–control study includes patients with recurrent epithelial ovarian cancer treated between March 2016 and April 2021 who progressed under PARP inhibitor maintenance. Data of patients treated with pegylated liposomal doxorubicin/trabectedin (experimental group) were matched 1:1 with a series of patients who received platinum-based treatment (control group). The study outcomes were overall clinical benefit (including complete, partial, and stable response), progression-free survival, and overall survival. The safety of both treatments was also evaluated. Results: A total of 26 patients in both groups were analyzed. Clinical benefit was achieved in 15 (57%) patients in the study group and 17 (65%) patients in the control group (p=0.38). Patients receiving pegylated liposomal doxorubicin/trabectedin had 5 months of progression-free survival, compared with 5 months in patients treated with platinum-based treatment (p=0.62). Patients in the experimental group achieved a median overall survival of 16 months compared with 19 months in the control group (p=0.26) There was no difference concerning severe toxicities (G3-G4) between groups, except for hepatic toxicity, which was experienced in 30% of the patients receiving pegylated liposomal doxorubicin/trabectedin and none in the control group (p<0.009). Conclusions: Pegylated liposomal doxorubicin/trabectedin might be an alternative option to platinum-based treatment in patients experiencing disease progression during PARP inhibitor maintenance with an acceptable toxicity profile. This might be a therapeutic option in this setting, sparing platinum compounds for subsequent relapse.